If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 9y = 66 Solving 3 + 9y = 66 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 9y = 66 + -3 Combine like terms: 3 + -3 = 0 0 + 9y = 66 + -3 9y = 66 + -3 Combine like terms: 66 + -3 = 63 9y = 63 Divide each side by '9'. y = 7 Simplifying y = 7
| 4x^2-5x-6.01=0 | | 100+100=h | | 10x+4-2x=14-4x+6+8x | | 3n-10=0 | | 3x-y=3d | | 8+(n+9)=21 | | Y=2x^3-14x^2+24x | | 4e+9=-63-8e | | 4(w-3)-2=-4(-6w+6)-8w | | (3n-5)(n-6)=0 | | 63-2e=14-9e | | 5-x=10x | | 33=6+3h | | 4e+6=-50-4e | | 5x+3y=182 | | 8+3e=6+e | | 6a+2=7a-1 | | 3e-2=13e-62 | | 9-8g=31 | | -x-8=4x-38 | | xy+2x=300 | | -4-8x+9x=12 | | .33x+10=0.6 | | -6+3y=-15 | | 3e+16=13e-94 | | (2cosx+1)(cosx+1)=0 | | -x^2-4x+32.01=0 | | 60p+50= | | 7u=4u+9 | | (X+7)(x+1)=(x+1) | | 35=-4d+7 | | (x-0.3)+(2x-0.2)+((40+x)-0.25)=274 |